Effect of the dibenzylbutyrolactone lignan (-)-hinokinin on doxorubicin and methyl methanesulfonate clastogenicity in V79 Chinese hamster lung fibroblasts - Resende, Flavia Aparecida [UNESP]; Tomazella, Iara Maluf; Barbosa, Lilian Cristina; Ponce, Marina; Furtado, Ricardo Andrade; Pereira, Ana Carolina; Bastos, Jairo Kenupp; Andrade e Silva, Marcio Luis; Tavares, Denise Crispim (Elsevier B.V., 2010)
The dibenzylbutyrolactone lignan (-)-hinokinin (HK) was obtained by partial synthesis from (-)-cubebin, isolated from the dry seeds of the pepper, Piper cubeba. In view of the trypanocidal activity of HK and its potential as a lead compound for drug development, evaluation of its possible genotoxic activity is required. We have tested HK for possible genotoxicity and evaluated the compound's effect on the activity of the clastogens doxorubicin (DXR) and methyl methanesulfonate (MMS) in the micronucleus (MN) assay with Chinese hamster lung fibroblast V79 cells. HK alone did not induce MN, at concentrations up to 128 mu M. In combined treatments, HK reduced the frequency of MN induced by MMS. With respect to DXR, HK exerted a protective effect at lower concentrations, but at higher concentrations it potentiated DXR clastogenicity. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Hinokinin; Micronucleus; V79 cell; Clastogenicity